EXAFS investigations of cobalt electrodeposition. (October 2020) - Lützenkirchen-Hecht, Dirk; Hamulić, Damir; Wagner, Ralph; Milošev, Ingrid
Abstract: X-ray absorption fine structure spectroscopy and scanning electron microscopy were used to study the atomic short range order structure, surface morphology and thickness of cobalt films electrodeposited from CoCl2 solutions on gold-coated Kapton. While the morphology on the electrodeposits strongly depends on the deposition time and thereby on the film thickness, the short range order structure deduced from the X-ray spectroscopic experiments suggests that pure metal films were formed, however with a slight relaxation of the Co-Co bond distances with increasing thickness, which may open new routes for the preparation of nanostructured Co-materials. Highlights: Electrodeposition from CoCl2-solution results in metallic Co films with different morphology dependent on the thickness. The growth rate determined from the evaluation of XANES experiments is equal to ca. 2 monolayers per second. Cobalt coordination appears to relax with increasing film thickness. Nanosized morphology may be maintained by repeated pulse deposition for larger film thickness.